Predicting General Aviation Pilots' Weather-Related Performance through a Scenario-Based Assessment. (September 2017) - Cruit, Jessica; Frederick, Christina; Blickensderfer, Beth; Keebler, Joseph R.; Guinn, Thomas
Weather-related accidents continue to challenge the general aviation (GA) community and with the development of advanced weather technology, GA pilots need additional education and training on how to effectively use these weather products to ensure flight safety. Currently, the literature on aviation weather suggests that there is a gap in both training and assessment strategy for GA pilots. Furthermore, several studies advocate assessing GA pilots at a deeper level of learning by including weather-based, scenario/application questions on the Federal Aviation Administration's (FAA) written exam for private pilots. After first developing a scenario-based, aviation weather assessment, we used a multiple regression analysis to predict aviation weather performance from 90 GA pilots. In addition, we used Baron and Kenny's (1986) test for mediation to predict aviation weather performance from four predictor variables (i.e., a scenario-based aviation weather assessment, a traditional, non-scenario-based weather assessment, weather salience, and aviation weather experience). The results of the study indicated that scores on the scenario-based assessment were the strongest predictor of aviation weather performance followed by aviation weather experience. These results support the need for scenario-based weather questions on the FAA written exam for private pilots. The results of this study could help aviation officials and educators better assess and train general aviation pilots on weather-related topics.